Biosynthesis and Production of Class II Bacteriocins of Food-Associated Lactic Acid Bacteria - Tingting Zhang; Yu Zhang; Lin Li; Xiuqi Jiang; Zhuo Chen; Fan Zhao; Yanglei Yi (Fermentation, 2022)
Bacteriocins are ribosomally synthesized peptides made by bacteria that inhibit the growth of similar or closely related bacterial strains. Class II bacteriocins are a class of bacteriocins that are heat-resistant and do not undergo extensive posttranslational modification. In lactic acid bacteria (LAB), class II bacteriocins are widely distributed, and some of them have been successfully applied as food preservatives or antibiotic alternatives. Class II bacteriocins can be further divided into four subcategories. In the same subcategory, variations were observed in terms of amino acid identity, peptide length, pI, etc. The production of class II bacteriocin is controlled by a dedicated gene cluster located in the plasmid or chromosome. Besides the pre-bacteriocin encoding gene, the gene cluster generally includes various combinations of immunity, transportation, and regulatory genes. Among class II bacteriocin-producing LAB, some strains/species showed low yield. A multitude of fermentation factors including medium composition, temperature, and pH have a strong influence on bacteriocin production which is usually strain-specific. Consequently, scientists are motivated to develop high-yielding strains through the genetic engineering approach. Thus, this review aims to present and discuss the distribution, sequence characteristics, as well as biosynthesis of class II bacteriocins of LAB. Moreover, the integration of modern biotechnology and genetics with conventional fermentation technology to improve bacteriocin production will also be discussed in this review.